Invasive shrubs differentially alter autumnal activity for three common small‐mammal species - Brian Connolly; Chad R. Zirbel; Carson Keller; Mark Fuka; John L. Orrock (Ecology, 2024)
Seasonal variation in animal activity influences fitness and the intensity of ecological interactions (e.g., competition, predation), yet aspects of global change in the Anthropocene may catalyze shifts in seasonal activity. Invasive plants are components of global change and can modify animal daily activity, but their influence on animal seasonal activity is less understood. We examined how invasive woody shrubs (Autumn olive [ Elaeagnus umbellata ] and Amur honeysuckle [ Lonicera maackii ]) affect seasonal activity of three common small‐mammal species by coupling experimental shrub removal with autumnal camera trapping for two consecutive years at six paired forest sites (total 12 plots). Eastern chipmunks ( Tamias striatus ) foraged more, and foraging was observed at least 20 days longer, in shrub‐invaded forests. White‐footed mice ( Peromyscus leucopus ) foraged more in invaded than cleared plots in one study year, but P. leucopus autumn activity timing did not differ between shrub‐removal treatments. Fox squirrel ( Sciurus niger ) activity displayed year‐specific responses to shrub removal suggesting intraannual cues (e.g., temperature) structure S. niger autumnal activity. Our work highlights how plant invasions can have species‐specific effects on seasonal animal activity, may modify the timing of physiological processes (e.g., torpor), and could generate variation in animal‐mediated interactions such as seed dispersal or granivory.